Effect of preservative in the physicochemical stability of cosmetic products based on natural resources from Costa Rican flora - Vargas Zúñiga, Rolando (2015)
A problem of rural women in Latin America is the poor access to economic resources; a solution we propose is to implement a collaborative model, where are used natural resources in the area for production of value added products such as cosmetics products,to improve their living conditions. Objective: This paper concerns the evaluation of the physicochemical stability of hair cosmetics based on natural resources of the Costa Rican flora. Methodology: cosmetic products were developed based on Carica papaya,Ananascomosus, and others from the area, equally developed stability testing at 25 ° C and 40 ° C for six months following the guidelines of ANVISA, and quality control which were adapted for reproduction on the production site. Results: Formulations designed contain at least 80% of natural excipients, but preservatives exclude parabens derivatives or other similar substances, also were quantified their physicochemical properties such as viscosity, specific gravity and pH, in different storage conditions during the time of the present study.Using ANOVA,was analyzed thedata. Conclusions: the study revealed that the formulations are stable for at least one year under the conditions of no more than 30°C and protected from light packaging, and achieved the respective health registry that allowed the marketing of the product.